STRATEGI PENGEMBANGAN PANTAI NIMTUKA SEBAGAI POTENSI WISATA BERBASIS MASYARAKAT DI DESA BONE, KABUPATEN KUPANG - Martarida Bagaihing; Christina Mariana Mantolas; Yudha Eka Nugraha (TOURISM: Jurnal Travel, Hospitality, Culture, Destination, and MICE, 2022)
This study aims to determine the potential of Nimtuka Beach in Bone Village so that it can be developed into a tourist destination, as well as to determine community-based development strategies for Nimtuka Beach in Bone Village, Nekamese District, Kupang Regency. This type of research uses descriptive qualitative, with the informant collection technique using purposive sampling technique. Data collection techniques were carried out by interviews, documentation, literature study, and observation. The analytical tool used to formulate a community-based tourism potential development strategy at Nimtuka Beach is a SWOT analysis by looking at the SWOT matrix. Based on the results of the SWOT analysis and the SWOT matrix, a community-based tourism potential development strategy at Nimtuka Beach can be formulated to make Nimtuka Beach a sport tourism, add supporting facilities, encourage local governments to improve road access, collaborate with local governments, increase human resources, increase promotional media through social media, and maintain cultural values.